Current status of dental journals published by Japanese organization - Haruto Hiraba; Yoshimasa Takeuchi; Kensuke Nishio; Hiroyasu Koizumi; Takayuki Yoneyama; Hideo Matsumura (Elsevier, 2024)
The publication status of dental journals in Japan was examined, with a focus on metrics such as Journal Impact Factor (JIF), Eigenfactor, Article Influence Score, and percentage of open access. A total of 18 journals published by Japanese dental organizations were identified in the Journal Citation Reports (JCR), with JIF values ranging from 0.4 to 6.6. The highest JIF was observed in The Japanese Dental Science Review. Additionally, 16 journals were not listed on the JCR. The authors explored the implications of these findings on the visibility and impact of Japanese dental research, and discussed the potential benefits of embracing open-access publications for greater global dissemination. This study highlighted the opportunities for journals to enhance their international recognition by meeting the criteria for JIF inclusion and embracing open-access publications. By adopting effective publication strategies, the dental community in Japan will be able to contribute to the advancement of dentistry globally, ensuring broader accessibility and recognition of its research contributions.